Analisis Risk dan Return Investasi pada Ethereum dan Saham LQ45 - Mutia Fitri Chania; Oyami Sara; Isfenti Sadalia (Studi Ilmu Manajemen dan Organisasi, 2021)
Purpose: This research aims to analyze the risk and return of investing in ethereum and LQ45 shares and to see the difference between LQ45 stock prices and ethereum prices before and after the announcement of the Covid-19 pandemic in Indonesia. Research Methodology: The research method uses the Kruskall-Wallis test and the Paired Sample t-test. Results: The results show the level of the return on ethereum and LQ45 shares did not have a significant difference, while the level of the risk between ethereum and LQ45 shares have a significant difference. For the price of Ethereum and LQ45 shares, there was a significant difference between before and after the Covid-19 pandemic was announced in Indonesia. The average price of ethereum and LQ45 shares decreased compared to before the announcement of the Covid-19 pandemic in Indonesia. Limitations: This research was conducted without including the risk-free rate in the calculation of stock risk. Contribution: This research is expected to be a reference for investors in viewed and analyzed investment opportunities based on risk and return during Covid-19.